2014
DOI: 10.7150/ijms.7634
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Quercetin against Oxidative Stress and Brain Edema in an Experimental Rat Model of Subarachnoid Hemorrhage

Abstract: Quercetin has been demonstrated to play an important role in altering the progression of ischemic brain injuries and neurodegenerative diseases by protecting against oxidative stress. The effects of quercetin on brain damage after subarachnoid hemorrhage (SAH), however, have not been investigated. This study was designed to explore the effects of quercetin on oxidative stress and brain edema after experimental SAH using four equal groups (n = 16) of adult male Sprague-Dawley (SD) rats, including a sham group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 51 publications
(51 reference statements)
6
74
0
2
Order By: Relevance
“…i.e., it has been reported that Caspase-3 expression was amplified in cortical neurons after brain ischemic injuries and inhibition of Caspase-3 reduces the neuronal loss and brain edema [20,21]. Our recent study also demonstrated that Caspase-3 is upregulated in in the rat hippocampus after CA [16].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…i.e., it has been reported that Caspase-3 expression was amplified in cortical neurons after brain ischemic injuries and inhibition of Caspase-3 reduces the neuronal loss and brain edema [20,21]. Our recent study also demonstrated that Caspase-3 is upregulated in in the rat hippocampus after CA [16].…”
Section: Introductionmentioning
confidence: 55%
“…Caspase-3 is a predominant target involved in the reactive oxygen species-mediated ischemia induced apoptosis in neuronal cells, and neuronal apoptosis results in blood brain barrier dysfunction, inflammation and oxidative cascades and thereby leading to brain damage [25,26]. It has been reported that Caspase-3 expression was exaggerated in cortical neurons after brain ischemic injuries and inhibition of Caspase-3 reduces the neuronal loss and brain edema [20,26]. In addition, a greater number of neurons that are stained with terminal deoxynucleotidyl transferase dUTP Nick End Labeling (TUNEL) are found in hippocampus as apoptosis is engaged in the pathological process of global ischemia-induced neuronal loss due to CA [14].…”
Section: Discussionmentioning
confidence: 99%
“…We used 18 male albino Wistar rats, about 2 months old, weighing 200-220 g to exclude possible protective effects of oestradiol against provoked oxidative stress (15,16 (4,(17)(18)(19)(20)(21) and correspond to the human daily dietary intake of quercetin and vitamin C enriched food and the daily nicotine intake in people who smoke 10-20 cigarettes per day (2,4).…”
Section: Experimental Designmentioning
confidence: 99%
“…Neuronal apoptosis result in blood brain barrier dysfunction, inflammation and oxidative cascades and thereby leading to brain damage [23,24]. It has been reported that Caspase-3 expression was exaggerated in cortical neurons after subarachnoid hemorrhage and inhibition of Caspase-3 reduces the neuron loss and brain edema [24,25]. Our current study showed that activated Caspase-3 by ICH was significantly attenuated by ICV infusion of ML288 stabilizing HIF-1α levels after induction of ICH.…”
Section: Discussionmentioning
confidence: 48%